2016
DOI: 10.1155/2016/1693918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traumeel (Tr14) on Exercise-Induced Muscle Damage Response in Healthy Subjects: A Double-Blind RCT

Abstract: The present double-blind, randomized, placebo-controlled clinical trial intended to test whether ingestion of a natural combination medicine (Tr14 tablets) affects serum muscle damage and inflammatory immune response after downhill running. 96 male subjects received Tr14 tablets, which consist of 14 diluted biological and mineral components, or a placebo for 72 h after the exercise test, respectively. Changes in postexercise levels of various serum muscle damage and immunological markers were investigated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
0
10
0
2
Order By: Relevance
“…On the other hand, Homeopathic Drug was reported to have bioregulatory effects in the treatment of acute musculoskeletal injuries [27,28]. Schneider [29] described the evidence of Homeopathic Drug's action on the inflammatory process, and of its efficacy and tolerability in randomized trials.…”
Section: Group Agentsmentioning
confidence: 99%
“…On the other hand, Homeopathic Drug was reported to have bioregulatory effects in the treatment of acute musculoskeletal injuries [27,28]. Schneider [29] described the evidence of Homeopathic Drug's action on the inflammatory process, and of its efficacy and tolerability in randomized trials.…”
Section: Group Agentsmentioning
confidence: 99%
“…The exact mechanisms of action are not known, but a number of studies suggest anti-inflammatory (Porozov et al, 2004 ; Birnesser and Stolt, 2007 ) and antioxidative properties (Baldwin and Bell, 2007 ; Zilinskas et al, 2011 ). Tr14 has shown effects on cellular and cytokine levels in randomized, double-blind controlled trials (RCTs) of exercise-induced muscle trauma (Pilat et al, 2015 ; Muders et al, 2016 , 2017 ), and demonstrated pain relief in acute ankle sprains (Gonzalez de Vega et al, 2013 ), with substantial evidence indicating a beneficial role in inflammation and wound repair (Wolfarth et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The more common treatment regimen described a few years later with the application of CFC and Tr14 in combination on day zero, two, and four after injury was described to result in a faster return-to-practice and return-to-play [19]. Tr14 was also demonstrated to have bio-regulatory effects in the treatment of musculoskeletal injuries in exercise induced inflammation [29][30][31][32], and comparable effectiveness to NSAIDs for the reduction in symptoms of inflammation [29].…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms could explain the protective properties of CFC injection therapy as observed clinically and in our animal studies following muscle tears. The ability of Tr14 to reduce inflammation [29][30][31][32] could be the potentiating effect that accelerates regeneration in the group administered the combined CFC and Tr14 therapy.…”
Section: Accelerated Muscle Regeneration After Combined Therapy With mentioning
confidence: 99%